Proxy warfare in strategic competition state motivations and future trends - Watts, Stephen; Frederick, Bryan A.; Chandler, Nathan 1982-; Toukan, Mark; Curriden, Christian; Mueller, Erik E.; Geist, Edward; Tabatabai, Ariane; Plana, Sara; Corbin, Brandon; Martini, Jeffrey (RAND Corporation, 2023)
The authors used both quantitative analysis and case studies of China, Iran, and Russia to examine the causes and likely future trends in proxy wars: civil wars in which at least one local warring party receives material support from an external state. The purpose of the project was to provide insight into the determinants of state support for violent nonstate actors, assess the risks that third-party support poses to U.S. overseas contingency operations, and analyze policy options available to the United States to counter such foreign support. With the renewed focus in many regions on strategic competition, there seems to be a growing risk that states will feel increasingly threatened by their rivals and take greater steps to counteract these threats in the years to come. The case studies highlight how such an environment can often, though not always, lead to an increased interest in supporting proxy warfare. Of even greater concern is the fact that geopolitical drivers of proxy warfare can often be self-reinforcing. The states considered in the case studies were usually able to develop at least a rudimentary capability for proxy warfare very quickly, within a couple of years, often building on the capabilities of prior efforts or regimes. Beyond this baseline capability, however, a relatively lengthy period of learning and growth to better develop proxy warfare capabilities appears to be common
"Prepared for the United States Army; approved for public release; distribution unlimited.
"RAND Arroyo Center.
Keywords: Proxy war / Forecasting; Proxy war / Case studies; Civil war / Case studies; Civil war; Proxy war; Case studies